Reading between the lines: Using media to improve German inflation forecasts - Benjamin Beckers; Konstantin A. Kholodilin; Dirk Ulbricht (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In this paper, we examine the predictive ability of automatic and expert-rated media sentiment indicators for German inflation. We find that sentiment indicators are competitive in providing inflation forecasts against a large set of common macroeconomic and financial predictors. Sophisticated linguistic sentiment algorithms and business cycle news rated by experts perform best and are superior to simple word-count indicators and autoregressive forecasts.
Keywords: C53; E31; E37; 330; inflation prediction; media sentiment indicators; news reports; real-time forecasting